2001
DOI: 10.1006/mare.2000.0139
|View full text |Cite
|
Sign up to set email alerts
|

Accounting information systems as knowledge-objects: some effects of objectualization

Abstract: This paper will outline a research methodology informed by theorists who have contributed to actor network theory (ANT). Research informed from such a perspective recognises the constitutive role of accounting systems in the achievement of broader social goals. Latour, Knorr-Cetina and others argue that the bringing in of non-human actants, through the growth of technology and science, has added immeasurably to the complexity of modern society. The paper "sees" accounting and accounting systems as being consti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0
4

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 80 publications
2
60
0
4
Order By: Relevance
“…Other studies reveal how accounting systems are products of mediation and translation. For example, casemix systems in a hospital appeared to be black-boxed systems ready for implementation but had to be modified to enrol support and became an actant that constructed a particular view of an organisation (Lowe, 2001); accounting in dynamic and complex business networks proved schizophrenic, producing shifting behaviours and notions of order within a short time which created instability not stability, and emergent and unintended rather than planned change (Thrane, 2007); accounting and calculative practices in a private equity value chain reflected dispersed, preordained beliefs and understandings, and appropriate means and ends rather than conventional methods prescribed in accounting texts (Nama and Lowe, 2014); and strategy was maintained by managing tensions and dialectical relationships between functional areas with conflicting goals and logics -although accountants were sometimes the custodians of the budgetary system, other functions acted as corporate policemen (Seal and Mattimoe, 2014).…”
Section: Post-structural Constructivist and Critical Contributionsmentioning
confidence: 99%
“…Other studies reveal how accounting systems are products of mediation and translation. For example, casemix systems in a hospital appeared to be black-boxed systems ready for implementation but had to be modified to enrol support and became an actant that constructed a particular view of an organisation (Lowe, 2001); accounting in dynamic and complex business networks proved schizophrenic, producing shifting behaviours and notions of order within a short time which created instability not stability, and emergent and unintended rather than planned change (Thrane, 2007); accounting and calculative practices in a private equity value chain reflected dispersed, preordained beliefs and understandings, and appropriate means and ends rather than conventional methods prescribed in accounting texts (Nama and Lowe, 2014); and strategy was maintained by managing tensions and dialectical relationships between functional areas with conflicting goals and logics -although accountants were sometimes the custodians of the budgetary system, other functions acted as corporate policemen (Seal and Mattimoe, 2014).…”
Section: Post-structural Constructivist and Critical Contributionsmentioning
confidence: 99%
“…In de zienswijze van ANT is technologie immers onlosmakelijk verweven met onze samenleving. Technologie, zoals MAC, zet mensen aan tot acties en andersom zullen menselijke actoren deze technische actoren zoveel mogelijk naar hun hand zetten voor eigen gebruik (Lowe 2001a;Lowe 2001b).…”
Section: Performativiteit Nader Geduid: Antunclassified
“…24 Casemix information systems were implemented as a tool to assist in providing data for the purpose of contracting between hospitals and their Regional Health Authority. Lowe 25,26 used a sociology of science (actor network theory) paradigm to describe the impact of the casemix information system on the behaviours of individuals at the organisational level within a large public hospital. Lowe,26 in his assessment of the impact of casemix, reported that, due to the complexity of DRG technology, clinicians who were unhappy with the output of the systems and the way these were used could do very little to challenge the systems (which is likened to a "black box").…”
Section: The Impact Of Casemix On Hospital Organisations and The Prodmentioning
confidence: 99%